Proceedings of the 20th ACM International Conference on Multimedia 2012
DOI: 10.1145/2393347.2396322
|View full text |Cite
|
Sign up to set email alerts
|

Music/speech classification using high-level features derived from fmri brain imaging

Abstract: With the availability of large amount of audio tracks through a variety of sources and distribution channels, automatic music/speech classification becomes an indispensable tool in social audio websites and online audio communities. However, the accuracy of current acoustic-based low-level feature classification methods is still rather far from satisfaction. The discrepancy between the limited descriptive power of low-level features and the richness of high-level semantics perceived by the human brain has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The authors recognized the need to introduce mid-level features in automatic music classification and thus design appropriates distances. Xi et al (2012) also addressed the problem where high-level features were derived from fMRI brain imaging.…”
Section: Common Featuresmentioning
confidence: 99%
“…The authors recognized the need to introduce mid-level features in automatic music classification and thus design appropriates distances. Xi et al (2012) also addressed the problem where high-level features were derived from fMRI brain imaging.…”
Section: Common Featuresmentioning
confidence: 99%
“…The authors reported that sound category information that is not detectable with conventional contrast-based analysis methods could be detected with multivoxel pattern analyses. In [49], the authors used fMRI to monitor the brain's response to natural music and speech listening and developed a computational framework to model the relationships between neuroimaging features and low-level acoustic features in the training dataset with fMRI scans. Then, they predicted neuroimaging features of a testing dataset without fMRI scans, and used the predicted neuroimaging features for music/speech classification.…”
Section: B Fmri-based Systems For Multimedia Analysismentioning
confidence: 99%
“…Existing systems that merged neuroimaging and multimedia, e.g., [26], [27], [49], assumed temporal stationarity of the brain's response for each multimedia clip, e.g., functional connectivities or other measurements were computed over the entire scan and used to characterize the brain's responses over the whole multimedia segment. However, [82] and [83] have shown that functional brain connectivities are under dynamic changes in different time scales.…”
Section: A Quantification Of the Brain's Responses: Opportunities Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there have been efforts in studying the neural basis of audio perception and understanding [10,11]. As reported in [10,11], music perception and understanding involve widely distributed human brain areas and functional interactions among large scale brain networks, which provide the theoretical foundation for deriving whole brain semantic features to perform low-level feature decoding.…”
Section: Introductionmentioning
confidence: 99%